Analysis of the Implementation of the Regulation of the Minister of Health Number 44 of 2016 concerning Public Health Center Management - Efendy, Ismail; Nyorong, Mappeaty; Himmah, Himmah (International Journal Papier Advance and Scientific Review, 2021)
The Regulation of the Minister of Health of Indonesia Number 44 of 2016 provides guidelines for puskesmas so that they can apply the puskesmas management pattern properly and correctly. The initial data obtained by the Pegasing Health Center has not fully implemented the Regulation of the Minister of Health of the Republic of Indonesia Number 44 of 2016 concerning management guidelines. The purpose of the study was to analyze the implementation of the Minister of Health Regulation Number 44 of 2016 concerning Public Health Center management at Pegasing Public Health Center, Central Aceh Regency. The research design used qualitative methods. The informant was the head of the puskesmas, the head of administration, the head of the admin, the head of the UKP, and the head of the UKM. The data were analyzed through the stages of reduction, data presentation and drawing conclusions. The results showed that planning, mobilization and implementation, monitoring control and performance appraisal were not carried out according to the Minister of Health No. 44 of 2016, the commitment was there but not all staff knew, the management team had not been formed, there was still a lack of staff awareness regarding the Minister of Health No. 44 of 2016. The conclusion of this study is that the Minister of Health Regulation No. 44 of 2016 does not work, organizational commitment has not been socialized, there is no management team formation, lack of concern, lack of solid team work. lack of staff knowledge and employee responsibilities.